2016
DOI: 10.13189/ujm.2016.040406
|View full text |Cite
|
Sign up to set email alerts
|

Tools and Techniques in Risk Identification: A Research within SMEs in the UK Construction Industry

Abstract: Risk identification plays a key role in the success of managing risk. Failure in the identification of risks can cause inadequacy in the whole process of risk management which led to non-achievement of organisational objectives. Tools and techniques facilitate the process of identification, and need to be adopted on the basis of firms' characteristics. The difficulty to recognise applicable tools and techniques within organisations is investigated as one of the key barriers that obstruct practise of risk manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 27 publications
0
27
1
1
Order By: Relevance
“…Of the 54 participants who responded to this question, 9.02% reported to use expert interviews to identify risks. This is in contrast to earlier findings by Rostami [26], who found that expert judgement is the second most used risk identification technique in the construction phase of projects with a 71% usage rate.…”
Section: 2113contrasting
confidence: 99%
See 2 more Smart Citations
“…Of the 54 participants who responded to this question, 9.02% reported to use expert interviews to identify risks. This is in contrast to earlier findings by Rostami [26], who found that expert judgement is the second most used risk identification technique in the construction phase of projects with a 71% usage rate.…”
Section: 2113contrasting
confidence: 99%
“…Some respondents indicated that cause and effect diagrams (7.52%) is used in their organizations. A minority of participants (6.77%) uses database or company documentation review method, which differ from Rostami [26] result were 75% of the respondents considered this technique as their most preferred tool for identifying risk. (6.01%) uses risk headings to identify risk in their projects.…”
Section: Hazop (Hazard and Operability Analysis) And Other Risk Identmentioning
confidence: 98%
See 1 more Smart Citation
“…For risk analysis, tools such as sensitivity analysis, probabilistic analysis, influence diagrams, and decision trees, as well as Delphi techniques, are commonly applied by construction practitioners (Chapman 2001;Zwikael and Ahn 2011;Adedokun et al 2013). Rostami (2016) discovered that the construction industry in the United Kingdom relies on the knowledge and experience of individuals for risk management.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Risk identification is important as it can assist an organisation to identify the best and most important input data; to have a better understanding on process and to identify the risks. Ultimately, risk identification provides information for decision-makers (Rostami, 2016). Therefore, this study develops the following research hypothesis: H1: Employees' understanding of risk identification process significantly influences their knowledge on risk management.…”
Section: Literature Reviewmentioning
confidence: 99%